Caracterização eletromecânica de compósitos de polímero e metal aplicados em sensores de deformação - Novaes, André Lucas (2018)
This work focuses on the characterization and study of a flex sensor composed of an electroactive material formed by an ionic polymer and metal. These materials can be applied in the development of artificial skin because they are light and flexible and because they have an expressive electromechanical response. In this work the study and electromechanical and electrical characterization of a composite formed by Nafion® and platinum electrodes were discussed. This material, when bent, produces an electrical signal that may be related to the magnitude and rate at which the material was folded. The general objective was to quantify the influence of the degree of hydration on the electric and electromechanical behavior of this electroactive composite. A system to control the relative humidity around the sample was developed to condition the samples under different conditions of degree of hydration. This system was coupled to an impedance spectroscopy module to evaluate the influence of the degree of hydration on the electrical properties of this material, and in another experiment, coupled to an electromechanical characterization module. This module consists of an actuator capable of folding samples in the form of a tape with angles and controlled velocities, and a system for collecting and amplifying the electrical signal produced in response to this deformation. The results of the electrical tests have shown that, typically, increasing the degree of hydration contributes to decreasing the impedance of the material. The electromechanical responses for step deformations showed a second order behavior and the intensity of the signal varied according to the degree of hydration and imposed deformation. For tests with oscillatory deformation, the samples presented a typical sinusoidal signal, with no finding of lag in relation to the mechanical stimulus. And that the increase in the degree of hydration led to an attenuation of the electromechanical signal.